2023
DOI: 10.3390/molecules28104135
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial Properties of Honey Bee Venom

Abstract: Due to its great medical and pharmaceutical importance, honey bee venom is considered to be well characterized both chemically and in terms of biomedical activity. However, this study shows that our knowledge of the composition and antimicrobial properties of Apis mellifera venom is incomplete. In this work, the composition of volatile and extractive components of dry and fresh bee venom (BV) was determined by GC-MS, as well as antimicrobial activity against seven types of pathogenic microorganisms. One-hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…BV is a defense tool of the hive against predators and is secreted by a gland located in the abdominal cavity of bees (Apis mellifera) [31,32]. For thousands of years, people have used bee products in various forms to treat diseases, with the curative effects being mentioned in the Holy Quran, the Bible, and the Veda [33]. BV was used medically in ancient Egypt and Greece, and in China, BV therapy has been known and applied for about 5000 years [33].…”
Section: Bee Venommentioning
confidence: 99%
See 1 more Smart Citation
“…BV is a defense tool of the hive against predators and is secreted by a gland located in the abdominal cavity of bees (Apis mellifera) [31,32]. For thousands of years, people have used bee products in various forms to treat diseases, with the curative effects being mentioned in the Holy Quran, the Bible, and the Veda [33]. BV was used medically in ancient Egypt and Greece, and in China, BV therapy has been known and applied for about 5000 years [33].…”
Section: Bee Venommentioning
confidence: 99%
“…For thousands of years, people have used bee products in various forms to treat diseases, with the curative effects being mentioned in the Holy Quran, the Bible, and the Veda [33]. BV was used medically in ancient Egypt and Greece, and in China, BV therapy has been known and applied for about 5000 years [33]. Historically, BV has generally been associated with the treatment of inflammatory conditions, rheumatism, and skin diseases, as well as malaria [34,35].…”
Section: Bee Venommentioning
confidence: 99%
“…In various studies, honey-BV has been identified for its antimicrobial properties against both bacteria and fungi [ 21 , 39 , 40 ]. Furthermore, recent research suggests that honey-BV possesses antimicrobial properties that could potentially be utilized in food preservation [ 41 ]. Therefore, using honeybee venom as a food preservative is a relatively novel concept that has gained some attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, increasing attention has been paid to propolis as an antidote to human microbial pathogens. In terms of antisepticity, propolis stands out among most other beekeeping products, second only to bee venom in terms of potency [6][7][8]. It exhibits a wide range of medicinal properties, which are not limited to antimicrobial action, as reflected in a number of recent comprehensive reviews [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%